Information technology and its use in distance education - Abdurahman Ibraheem Hamd Algantossi; Barzan Moyasir Hamid Alhameed (Journal of Madenat Alelem University College, 2022)
The study deals with the concept of educational technology, that is, the modern technologies used in the educational process and its impact on supporting and developing the quality of distance education, and its most prominent characteristics and impact on that, and what are the pros and cons resulting from its use, as well as the importance of integrating modern technology into education and the most prominent pros and cons that can result from that.